Recent Progress in Textile-Based Flexible Supercapacitor - Awais Sattar Ghouri; Rabya Aslam; Muhammad Saqib Siddiqui; Syed Kamran Sami (Frontiers in Materials, 2020)
In the backdrop of the growing requirement of flexible and wearable energy storage systems, textile-based supercapacitors having characteristic flexibility, superior charging-discharging rates, and low cost are ideal energy storage devices for wearable applications. Lightweight and flexible textile-based supercapacitors characterized by high conductivity, thermal, and environmental stability with negligible degradation under repeated use are required for multifunctional wearable electronics. Herein, supercapacitor based upon textile fabrics will be reviewed from the perspective of electrochemical, mechanical, and thermal properties without compromising flexibility, durability, and comfort of textile fabric.